Gel‐like inclusions of C‐terminal fragments of TDP‐43 sequester stalled proteasomes in neurons. (19th April 2022) - Riemenschneider, Henrick; Guo, Qiang; Bader, Jakob; Frottin, Frédéric; Farny, Daniel; Kleinberger, Gernot; Haass, Christian; Mann, Matthias; Hartl, F. Ulrich; Baumeister, Wolfgang; Hipp, Mark S; Meissner, Felix; et al.
Abstract: Aggregation of the multifunctional RNA‐binding protein TDP‐43 defines large subgroups of amyotrophic lateral sclerosis and frontotemporal dementia and correlates with neurodegeneration in both diseases. In disease, characteristic C‐terminal fragments of ~25 kDa ("TDP‐25") accumulate in cytoplasmic inclusions. Here, we analyze gain‐of‐function mechanisms of TDP‐25 combining cryo‐electron tomography, proteomics, and functional assays. In neurons, cytoplasmic TDP‐25 inclusions are amorphous, and photobleaching experiments reveal gel‐like biophysical properties that are less dynamic than nuclear TDP‐43. Compared with full‐length TDP‐43, the TDP‐25 interactome is depleted of low‐complexity domain proteins. TDP‐25 inclusions are enriched in 26S proteasomes adopting exclusively substrate‐processing conformations, suggesting that inclusions sequester proteasomes, which are largely stalled and no longer undergo the cyclic conformational changes required for proteolytic activity. Reporter assays confirm that TDP‐25 impairs proteostasis, and this inhibitory function is enhanced by ALS‐causing TDP‐43 mutations. These findings support a patho‐physiological relevance of proteasome dysfunction in ALS/FTD. Synopsis: TDP‐25, a C‐terminal fragment of TDP‐43 found in ALS and FTD patients, forms cytoplasmic inclusions with gel‐like properties in primary neurons. Proteasome enrichment and impaired proteostasis support the relevance of proteasome dysfunction in ALS/FTD. neuronal cytoplasmic TDP‐25 inclusions adopt an amorphous gel‐like state without detectable fibrils stalled proteasomes are present in the inclusions multiple ALS‐causing mutations further increase proteasomal impairment Abstract : TDP‐25, a C‐terminal fragment of TDP‐43 found in ALS and FTD patients, forms cytoplasmic inclusions with gel‐like properties in primary neurons. Proteasome enrichment and impaired proteostasis support the relevance of proteasome dysfunction in ALS/FTD.